2017
DOI: 10.1063/1.4978351
|View full text |Cite
|
Sign up to set email alerts
|

Durability of thermochemical heat storage demonstrated through long-term repetitive CaCl2/H2O reversible reactions

Abstract: Thermochemical heat storage is a promising technology for improving thermal energy efficiency. In this study, CaCl2 and H2O were selected as the reactant and working medium, respectively, assuming the utilization of low-grade waste heat. To investigate the durability of the CaCl2/H2O reaction, 1000 repetitive operations were conducted at the same 110 °C charging and discharging temperatures. During the long-term repetitions, a decrease in the average volumetric power density was observed. The peak value in rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, during heat storage, the outlet temperature of the heat exchange fluid was lower than the inlet temperature. To compare the SiC honeycomb-and aluminum corrugated fin-type reactors [6]. The heat output and conversion ratio is shown in Figure 4.…”
Section: Results Of Heat Release and Storage Behavior And Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during heat storage, the outlet temperature of the heat exchange fluid was lower than the inlet temperature. To compare the SiC honeycomb-and aluminum corrugated fin-type reactors [6]. The heat output and conversion ratio is shown in Figure 4.…”
Section: Results Of Heat Release and Storage Behavior And Discussionmentioning
confidence: 99%
“…The CaCl 2 /H 2 O reaction system was adopted, which involves a reversible chemical endothermic or exothermic reaction, as follows. The material used in this system is environmentally sustainable, commonly used, readily available, nontoxic, and chemically stable [6], and the working temperature is below 200˚C. Moreover, the CaCl 2 /H 2 O reaction system has already been studied for chemical heat storage, and the potential use of both sides of the reversible CaCl 2 /H 2 O reaction has been demonstrated in previous studies [6].…”
Section: Introductionmentioning
confidence: 99%
“…For chemical heat storage materials, CaCl 2 and H 2 O were selected as the reactant and working medium, assuming the utilization of low-grade waste heat [6]. Li et al investigated the hydration and dehydration reaction of lithium hydroxide (LiOH) for low temperature heat sources [7].…”
Section: Introductionmentioning
confidence: 99%
“…Among these technologies, the chemical heat pump (CHP), driven by reversible chemical reactions, is a promising technology for contributing to the need to utilize thermal energy. Studies have suggested a number of natural high-affinity refrigerant and reactant pairs, including H 2 O [9], NH 3 [10], and CO 2 [11] for refrigerants and solid oxides and metal halides for reactants. To date, CHPs have been investigated in a number of cycle modes, namely heat storage, heat upgrading, and chiller heat modes.…”
Section: Introductionmentioning
confidence: 99%